Evolution of livelihood vulnerability in rice terrace systems: Evidence from households in the Ziquejie terrace system in China - Deng, Chuxiong; Wang, Shuyuan; Liu, Yaojun; Li, Zhongwu; Zhang, Guangye; Li, Wenqing; Liu, Changchang (Frontiers in Sustainable Food Systems, 2023)
Introduction Globally, terraces, and rice terrace systems face problems that affect their sustainability, such as terrace degradation, abandonment, de-agriculturalization, labor migration, etc. The implementation of development projects such as reforestation, poverty alleviation, and tourism development have changed traditional smallholder livelihood patterns. It is not clear whether farmers' livelihoods have become more resilient or vulnerable as a result. Methods Using survey data on households' livelihoods in a rice terrace system in Southern China, we evaluated the livelihood impacts of multiple changes. Results The results show that development projects are not entirely beneficial. The attributes and intensity of the disturbance of projects (e.g., tourism) on land functions, and differentiated farmer strategies jointly drive the hierarchical evolution of livelihood vulnerability. In detail, underdeveloped tourism increased rather than reduced livelihood vulnerability; the role of agriculture in livelihood directly exacerbated the variation in vulnerability levels; this resulted in the most vulnerable livelihood for households that are exogenously dependent or located in the core tourism area. Discussion Subsequently, an evolutionary model of livelihood vulnerability is proposed in this study. Based on this, we judged that the livelihood vulnerability of rice terrace systems has entered a chaotic stage of adaptation. Reducing livelihood vulnerability will require the support of a tangible and circular pathway of benefits between farmers and the land. Policies should focus on the heterogeneity of farmers and the “negative effects” of development projects on livelihood. This household-level farmer livelihood vulnerability dynamics study goes beyond anti-poverty to provide science-based practical guidance to promote the sustainable development of rice terrace systems.